HALAL INDUSTRY IN KYRGYZSTAN: CURRENT STATE AND DEVELOPMENT PROSPECTS - Niyazali Turdalievich Aripov; Murat Zhuratovich Abdiev; Ahmad Syukran Baharuddin; Mirlanbek Baidusenovich Ubaidullaev (Malaysian Journal of Syariah and Law)
The halal industry in the Kyrgyz Republic faces a low level of development despite its great potential for economic growth and international market integration. The lack of adequate infrastructure, inefficiencies in the value chain, a lack of coordination among market participants (private sector, government authorities and foreign investors) and an inadequate legal framework are hindering the industry's progress. This study aims to identify these obstacles and propose solutions to promote the development of the halal industry through innovative investments and the adoption of global best practises in the Kyrgyz Republic. This study employs qualitative methodology through documentary method to collect the data and content analysis method to analyse the data. In the course of this study, factors and conditions for the low level of development of the halal industry in the Kyrgyz Republic were identified and standard regulatory frameworks were proposed. It was examined whether it is necessary to create an appropriate infrastructure, increase the efficiency of the value chain, integrate the participants of the halal market: the private sector, government agencies and foreign investors, improve the qualifications and skill of workers, introduce an automated traceability system for halal products, introduce rules for trading halal products in retail establishments and implement a control system. The subject of the study are the organisational and economic mechanisms of the halal industry in the Kyrgyz Republic where the development of the halal industry relies on the basis of innovative investments by orienting themselves on international standards. The use of theoretical and practical recommendations. The essence and content of the halal industry were determined, after studying the markets of the countries of Europe and the United Stats of America (USA), problems were identified and necessary mechanisms for solving problems in the release of halal products were recommended. In addition, the appropriate application of the recommendations will create the necessary conditions for a large-scale analysis of the halal industry in the Kyrgyz Republic, which in turn will solve the existing problems in this industry.